Dynamic Risk Management Strategies: Adapting Financial Practices in the Face of Global Economic Uncertainty - Wellia Novita; Gustia Harini; Devi Edriani (Pusat Riset dan Inovasi Nasional, 2025)
Multinational corporations operating in high volatility industries are increasingly exposed to global economic disruptions, making financial stability a critical strategic priority. Despite the adoption of Dynamic Risk Management (DRM) strategies to address such challenges, the impact of DRM on financial performance remains insufficiently understood, especially under extreme macroeconomic uncertainty. This study aims to explore how DRM contributes to financial performance and how this relationship is moderated by Global Economic Uncertainty (GEU). Using a qualitative exploratory case study design, data were gathered through semi structured interviews with finance and risk executives from firms in the energy, manufacturing, and technology sectors, supported by analysis of internal documents and risk reports. Thematic analysis revealed that DRM practices such as real time monitoring, dynamic hedging, and predictive analytics are essential in stabilizing liquidity, profitability, and operational continuity. However, their effectiveness is contingent upon firms’ strategic adaptability and the severity of external economic shocks. The conceptual model developed positions GEU as a critical moderating variable and emphasizes the role of agile governance and scenario planning in enhancing DRM outcomes. These findings synthesize the theoretical and practical link between DRM and financial performance, suggesting that firms must go beyond technical risk tools and embed strategic agility into their risk governance frameworks. The study contributes to the literature by integrating financial resilience, adaptive capability, and external uncertainty into a unified analytical framework, offering practical insights for corporate leaders in turbulent economic environments.